Testing the positional accuracy of OpenStreetMap data for mapping applications - El-Ashmawy, Khalid l. A. (Geodesy and Cartography, 2016)
OpenStreetMap, a web mapping platform, is the most popular web map source for use in locationbased services with specific emphasis on pedestrian navigation, tourist guide applications, and other location-based search applications. This paper tests the positional accuracy of OpenStreetMap for the mapping applications using the case study in the campus of UMM El-Qura University, Makah, Saudi Arabia. The proposed testing method consists of statistical comparative approach using OpenStreetMap data and accurate land surveying reference data. The results show that OpenStreetMap data has positional accuracy of 1.57 m which is suitable for generating planimetric maps of scale 1:5000 or smaller. The obtained results open the door for using the OpenStreetMap maps for applications such as general preliminary planning where larger areas are covered but only moderate accuracy is needed. Applications include mapping the general layout of potential construction sites, proposed transportation systems, and existing facilities. The proposed methodology in this paper is of great interest to small engineering firms for the generation of local area maps from OpenStreetMap data.